THE RELATIONSHIP OF SELF-CONFIDENCE TO INDEPENDENCE IN LEARNING INDONESIAN CLASS 3 AT SDN MANGUN JAYA 03 - Ningsih, Niviana; Dariyanto, Dariyanto (PROGRES PENDIDIKAN, 2024)
If students experience low self-confidence, if it cannot be handled properly, it will result in low learning independence and can hinder students' progress in the learning system. Therefore, the problem that will be studied in this research is: "Is there a significant relationship between self-confidence and student learning independence in Indonesian language subjects in class 3 at SDN Mangun Jaya 03". This type of research is quantitative and correlational based. This research was conducted in class III (A, B, C, D) of SDN Mangunjaya 03 semester 2 (even) of the 2023/2024 academic year with a population of 112 students. Researchers used cluster random sampling techniques with a minimum sample of 56 respondents. In the trial of the self-confidence variable instrument, only 25 valid items were obtained from 30 question items, while the learning independence variable only found 20 valid items from 24 question items, and all reliability test results were met. The prerequisite test results showed that the normality and linearity tests had been fulfilled. The correlation test result between the self-confidence variable and the learning independence variable is 0.432, which has a positive value and is included in the medium relationship level category. In conclusion, there is a significant relationship between self-confidence and student learning independence in Indonesian language subjects in class 3 at SDN Mangun Jaya 03.